A stability-indicating HPLC assay of ten different vitamins in a food supplement: Appraisal of the method's greenness, whiteness, and blueness - Abdelfatah, Rehab M.; Abd Elhalim, Lobna Mohammed; Darwish, Hany W.; Ayoub, Bassam M.; Tony, Rehab Moussa; Gamal, Mohammed (Talanta (Oxford), 2024)
Due to their susceptibility to degradation, vitamin levels in food formulations may differ from those found in the finished product. Vitamin levels can be impacted by processing and storage. In this work, the ingredients of Strong B50 ® film-coated tablets were estimated simultaneously using simple efficient stability indicating HPLC method. Strong B50 ® film-coated tablets contain thiamine (VB1), riboflavin (VB2), calcium pantothenate (VB5), pyridoxine (VB6), vitamin C (VC), folic acid (FA), biotin (BT), inositol (IS), niacin (NC), para-aminobenzoic acid (PB), cyanocobalamine (B12), choline bitartarate, and iron gluconate. Hypersil BDS C18 column was used for achieving reasonable separation. Mobile phases (A) and (B) were utilized, the mobile phase (A) consisted of 0.015 M Hexane sulfonic acid sodium salt + 0.1 % Triethylamine and orthophosphoric acid was used to adjust the pH to (2.9) while (B) system consisted of acetonitrile. Validation of the method was assessed using International Conference of Harmonization (ICH) parameters, where linearity, accuracy, selectivity, and robustness of the method were investigated. Correlations were above 0.99, accuracy results ranged from 97.6 to 102.8 % and limits for detection and quantitation (LOD and LOQ) values were determined for each vitamin in μg/mL except for FA and BT in ng/mL. LOD values were between 0.006 and 15.08 μg/mL while LOQ values ranged from 0.031 to 49.77 μg/mL. Stability studies were conducted under stressed conditions and degradation percentages were computed. Where, VB5, VB6, FA and PB, VC, and NC were the most degradable vitamins. Whiteness evaluation using the modern RGB 12 algorithm compared our method and the old reported one by Sasaki et al., 2020. The comparison favored our newly developed method in terms of analytical performance, practical applicability and greenness. Besides, AGREE and GAPI soft wares were used to assess the greenness of the method. It was clear that the results of colored pictograms confirm low hazardous impact and that the new method is greener with AGREE score of 0.66. Furthermore, the functionality and applicability of the novel HPLC approach were concluded via the Blue Applicability Grade Index (BAGI) tool with a final score of 82.5. [Display omitted] •Ten vitamins were estimated simultaneously, despite the variability in concentrations and structures by a green HPLC method.•Whiteness assessment for the method was applied for evaluation and comparison with the reported related one.•Stability studies have been conducted for the ten vitamins under different conditions.•The applicability and the functionality of the novel approach was concluded via the new BAGI tool.